Dois exercícios de política monetária e fiscal com atuação ótima do Banco Central - Faria, Ricardo Meirelles de (2007)
The thesis is about coordination problem between monetary and fiscal policy within the Brazilian inflation targeting regime. A set of fiscal equations is incorporated into a small open economy inflation targeting model in order to study the impact to the monetary and fiscal policy reaction functions when different schemes of coordination are taken. Using Leeper´s (1991) concepts, both agencies, Central Bank and Treasury, can act in active or passive form and there will be this strategic behavior that will determine the efficiency of the monetary policy. The parameters of the model were estimated and calibrated to the Brazilian economy in order to simulate some kind of shocks that have affected Brazil in these last years. The results show that the schemes of coordination in which the fiscal authority reacts to changes in public debt, increasing the primary surplus, the adjustment path of the variables to shocks tend to be, in almost all cases, less volatile indicating a more efficient Central Bank. In these regimes the Central Bank does not have to assume tasks that are inherent to the Treasury. It is also analyzed the variations in the behavior of the monetary and fiscal authority due to different structures of the public debt. The results show that the composition of the debt will be beneficial or not depending on the king of shock confronted with. The first chapter discusses the main questions that the thesis intends to investigate and in the second part it presents a brief description of the last eight years of economy of Brazil. In chapter two it is analyzed the fundamentals of an inflation targeting regime and their main components; it is also discussed the necessary fiscal policy rules to the achievement of price stability as well as the main theories that study a possible existence of fiscal dominance trap in the conduction of the economical policy of Brazil in recent years. Chapter three presents the incorporation of the fiscal block into the small open economy inflation targeting model proposed in Svensson (2000) and its estimation and calibration. The chapter four discusses the different schemes of coordination to the monetary and fiscal policy and the optimal reaction function of the Central Bank. Based on the most efficient scheme obtained in the previous chapter the fifth chapter studies the changing in the behavior of the Central Bank and Treasury when confronted with different compositions for the public debt, differences that affect its interest rate, inflation and exchange rate elasticities.